1991
DOI: 10.1001/jama.1991.03460140061027
|View full text |Cite
|
Sign up to set email alerts
|

The Hypocholesterolemic Effects of β-Glucan in Oatmeal and Oat Bran

Abstract: Oat cereals rich in the water-soluble fiber beta-glucan have been studied as a dietary therapy for hypercholesterolemia. To determine the hypocholesterolemic response of beta-glucan in the diet, 156 adults with low-density lipoprotein cholesterol (LDL-C) levels above 4.14 mmol/L (160 mg/dL) or between 3.37 and 4.14 mmol/L (130 and 160 mg/dL) with multiple risk factors were randomized to one of seven groups. Six groups received either oatmeal or oat bran at doses (dry weight) of 28 g (1 oz), 56 g (2 oz), and 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(64 citation statements)
references
References 19 publications
0
63
0
1
Order By: Relevance
“…In the majority of reports (Table 4) there appears to be a tendency to a dose-response effect, though even in the bestdesigned trial (Davidson et al, 1991) this was rather inconsistent. Two estimates have been published of the size of the average cholesterol-lowering effect.…”
Section: (B) Experiments On Effects Of Cereal Foods or Fractions On Rmentioning
confidence: 99%
“…In the majority of reports (Table 4) there appears to be a tendency to a dose-response effect, though even in the bestdesigned trial (Davidson et al, 1991) this was rather inconsistent. Two estimates have been published of the size of the average cholesterol-lowering effect.…”
Section: (B) Experiments On Effects Of Cereal Foods or Fractions On Rmentioning
confidence: 99%
“…Of particular interest has been the effects of oat soluble fibers in reducing cholesterol levels in hypercholesterolemic patients (de Groot et al 1963;Anderson et al 1984), their effects on blood sugar levels, especially insulin needs in diabetic patients (Jenkins et al 1981;Wood et al 1988), and their impact on cancer of the colon and related gastrointestinal disorders (National Research Council 1989). These beneficial effects have been primarily attributed to 1→3, 1→4-β-D-glucans (Davidson et al 1991).…”
mentioning
confidence: 99%
“…There is an average reduction of 11% in the plasma total on consumption of 140 g of rolled oats (Poinerou et al 2001). The FDA claim for oat determined that an effective daily intake of β-glucan for controlling serum cholesterol level is 3 g. This can differ among different individuals and depends upon initial cholesterol content of the subject (Davidson et al 1991). Awika and Rooney (2004) reported that guinea pig fed with 58% low tannin sorghum was more beneficial in lowering cholesterol than rolled oats, wheat or pearl millet.…”
Section: Cardiovascular Diseases (Cvd)mentioning
confidence: 99%